Advances in Activation of Persulfate by Novel Carbon-Based Materials: Degradation of Emerging Contaminants, Mechanisms, and Perspectives - Lianghui Guo; Dong Liu; Runyao Han; Aoxiang Yin; Guifan Gong; Shi Li; Ruixuan Chen; Jianyu Yang; Zimeng Liu; Keke Zhi (Crystals)
Global industrialization has intensified the emission of emerging contaminants (ECs), posing a serious threat to the environment and human health. Persulfate-based advanced oxidation processes (PS-AOPs) have become a research hotspot due to their efficient degradation capability and environmentally friendly features; carbon-based materials are ideal catalysts for activating persulfate (PS) due to their tunable electronic structure, abundant active sites, and low cost. This study summarizes the application of carbon-based materials (graphene, single-atom catalysts (SACs), etc.) in PS-AOPs, and provides insights into the degradation mechanisms of radicals (e.g., sulfate radical (SO4−·), hydroxyl radical (·OH)) and non-radicals (e.g., 1O2(singlet oxygen), electron transfer). The removal efficacy of carbon-based catalysts for antibiotics, phenols, and dyes was compared, and the key degradation pathways were elucidated. In addition, the activation of PS can be accelerated, and catalytic efficiency can be improved by synergizing with ancillary technologies (e.g., light, electricity). Despite the great potential of carbon-based catalysts, their large-scale application is limited by the complexity of the catalyst preparation process and the lack of selectivity for complex water qualities. Future studies can accelerate the practical application of PS-AOPs in wastewater treatment through the precise design of SACs and the construction of multi-mechanism synergistic activation systems.